Consejo Editorial (Revista de Historia, 2015)
Editor Pablo Scatizza (Universidad Nacional del Comahue) Consejo de Edición Cecilia Azconegui (Universidad Nacional del Comahue); Norma García (Universidad Nacional del Comahue); Miguel Ángel Jara (Universidad Nacional del Comahue) Carla Mannara (Universidad Nacional del Comahue); Joaquín Perren (Universidad Nacional del Comahue – CONICET); Ariel Petruccelli (Universidad Nacional del Comahue); Andrea Rodríguez (Universidad Nacional del Comahue); Sofía Stefenalli (Universidad Nacional del Comahue); Esteban Vedia (Universidad Nacional del Comahue) Comité Académico Omar Acha (Universidad de Buenos Aires - CONICET), Argentina; Samuel Amaral (Universidad Nacional Tres de Febrero), Argentina; Waldo Ansaldi, (Universidad Nacional de La Plata), Argentina; Susana Bandieri, (Universidad Nacional del Comahue- CONICET), Argentina; Marta Bonaudo (Universidad Nacional de Rosario -CONICET), Argentina; Atilio Boron (FLACSO), Argentina; Gerardo Caetano (Universidad de la República de República), Uruguay; Lila Caimari (Universidad de San Andrés), Argentina; Guillermo Mira Delli-Zotti (Universidad de Salamanca) España; Orietta Favaro (Universidad Nacional del Comahue), Argentina; Enrique Mases, (Universidad Nacional del Comahue), Argentina; Maria Estela Spinelli (Universidad Nacional del Centro de la Provincia de Bs. As.), Argentina; Maristella Svampa (Universidad de Buenos Aires - CONICET), Argentina; César Tcach (Universidad Nacional de Córdoba - CONICET), Argentina; Sergio Grez Toso (Universidad de Chile)